KENAF : ITS PROSPECT IN INDONESIA - Estri Laras Arumingtyas (The East Java Biological Society, 2015)
Kenaf is a plant fibre with high potential as source of material industry. Originally, kenaf usage in Indonesia is still limited only for jute sacks material, which is then displaced by plastic sacks production. While at international scale, kenaf has been started to be developed as pulp material, polypropylene composite, fibreglass replacement, and particle board for automotive industry materials. Indonesia is a tropical country this condition which suitable for kenaf cultivation. However, research reports about kenaf potential usages are still few and limited in domestic level only. Whereas, Indonesian kenaf plant information is needed by international community to understand comprehensively about the potential of tropical plants. This article aims to provide an overview about kenaf cultivation potential and usages in Indonesia as well as the possibility of future development.